Multifunctional urban flood resilience enhancement strategies - Mugume, Seith N.; Melville-Shreeve, Peter; Gomez, Diego; Butler, David (Thomas Telford Ltd, 2017)
Enhancing resilience in urban drainage systems (UDSs) can be achieved by implementing a range of strategies that minimise the magnitude and duration of flooding during or after the occurrence of unexpected system failures. Dual-purpose rainwater harvesting (RWH) systems provide a promising multifunctional resilience-enhancing strategy due to their associated multiple benefits such as water conservation and distributed control of storm water. However, their effectiveness in respect to minimisation of resulting flooding impacts and provision of alternative water supplies during unexpected system failures has not been explicitly investigated at a city district or catchment scale. This paper applies the global resilience analysis approach to investigate the effect of implementing a set of multifunctional RWH strategies on improvement of UDS resilience to random cumulative link (sewer) failure, using a case study of the Nakivubo system in Kampala, Uganda. The resulting water supply resilience enhancement benefits are also investigated. The study results reveal that catchment-scale implementation of suitably designed RWH systems provides an effective strategy that improves the system’s global resilience to flooding by up to 25%, while simultaneously providing up to 30% of the household water supply requirements in the case study area.
Keywords: failure; floods; flood works; sustainability